Site-specific additionality in aboveground carbon sequestration in set-aside forests in Flanders (northern Belgium) - Vanhellemont, Margot; Leyman, Anja; Govaere, Leen; De Keersmaeker, Luc; Vandekerkhove, Kris (Frontiers in Forests and Global Change, 2024)
In situ carbon sequestration in forests is important in the context of climate change mitigation, and setting aside managed forests has been proposed as an option for increased carbon sequestration. Comparing set-aside and managed forests may provide insights and rules of thumb on the potential for additional in situ carbon sequestration in set-aside forest.In an observational study, we compared re-inventory data from the network of set-aside forest reserves in Flanders, which have been unmanaged for 17-66 years (2 surveys with a 10 year interval), with re-inventory data from the regional forest inventory, representing the overall forest area in Flanders (2 surveys with a 15-year interval).The aboveground carbon pools and sequestration rates were higher in the set-aside forests compared to the average forest in Flanders. In the average Flemish forest, the aboveground carbon pool increased from 64.7 to 85.1 tC ha -1 , over a period of 15 years. In the set-aside forests, the mean pool was higher at the first measurement and further increased from 84.8 to 102.4 tC ha -1 , over a period of 10 years. The mean aboveground annual carbon sequestration rate was 1.3 tC ha -1 yr -1 in the average forest in Flanders and 1.8 tC ha -1 yr -1 in the set-aside forests. The stocks and fluxes depended on the soil conditions and were higher in set-aside forests on silt and sandy silt sites compared to wet and sand sites. The set-aside forests on dry sites showed additionality in in situ aboveground carbon sequestration . We saw no indication of approaching a culmination point in the first decades following set-aside: plots with high carbon pools did not show lower carbon sequestration. In conclusion, set-aside forests can combine high carbon pools with high sequestration rates on suitable sites. Under the current management policy, we expect Flemish forests -regular and set-aside -to further increase their carbon pools in the coming decades.